2014
DOI: 10.4049/jimmunol.1401114
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Inhibits the Effector Functions of Activated NK Cells via the Upregulation of the D5 Receptor

Abstract: Several lines of evidence indicate that dopamine (DA) plays a key role in the cross-talk between the nervous and immune systems. In this study, we disclose a novel immune-regulatory role for DA: inhibition of effector functions of activated NK lymphocytes via the selective upregulation of the D5 dopaminergic receptor in response to prolonged cell stimulation with rIL-2. Indeed, engagement of this D1-like inhibitory receptor following binding with DA suppresses NK cell proliferation and synthesis of IFN-γ. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
(107 reference statements)
1
27
0
1
Order By: Relevance
“…Though perhaps surprising at first glance, these results are consistent with the notion of the dopamine-mediated control of lymphocyte function [26]. For instance, the significant decline in NK-cells could be explained by the suppression of NK-cell proliferation following prolonged dopamine-induced activation [27], which would be a plausible scenario Another study, which also administered cocaine to their volunteers in vivo before challenging their blood in vitro with LPS reported that cocaine had a significant inhibitory effect on the secretion of TNF- whilst preserving the secretion of IL-6 [34]. However, we could not replicate the aforementioned findings in our own data, which we obtained by stimulating blood samples of healthy volunteers in vitro with PHA and LPS both with and without using cocaine as a co-stimulator.…”
Section: Infections Due To Drug Effects On Cell-mediated Immunitysupporting
confidence: 82%
“…Though perhaps surprising at first glance, these results are consistent with the notion of the dopamine-mediated control of lymphocyte function [26]. For instance, the significant decline in NK-cells could be explained by the suppression of NK-cell proliferation following prolonged dopamine-induced activation [27], which would be a plausible scenario Another study, which also administered cocaine to their volunteers in vivo before challenging their blood in vitro with LPS reported that cocaine had a significant inhibitory effect on the secretion of TNF- whilst preserving the secretion of IL-6 [34]. However, we could not replicate the aforementioned findings in our own data, which we obtained by stimulating blood samples of healthy volunteers in vitro with PHA and LPS both with and without using cocaine as a co-stimulator.…”
Section: Infections Due To Drug Effects On Cell-mediated Immunitysupporting
confidence: 82%
“…Dopamine regulates NK cell cytotoxicity through the cAMP-PKA-CREB signaling pathway (Zhao et al 2013). By binding to DR5, dopamine exerts an inhibitory function to 'switch-off' activated natural killer (NK) cells (Mikulak et al 2014). Central memory T cells (T CM ) and effector memory T cells (T EM ) express more D2-than D1-like receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, neurotransmitters have been extensively studied, especially monoamines in the central and peripheral immune systems. Dopamine, a catecholamine, exerts its function by targeting specific DR to modify the activation (Mikulak et al 2014), proliferation (Saha et al 2001), differentiation (Nakano et al 2009a,b), chemotaxis, homing (Watanabe et al 2006) and apoptosis of immune cells (Oberbeck et al 2006). The five DRs, termed DR1, DR2, DR3, DR4, and DR5, are G-protein coupled receptors that can be further categorized into two classes based on their ability to modulate cyclic adenosine monophosphate (cAMP) production, the D1-like (DR1 and DR5) and D2-like (DR2, DR3, and DR4) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…To date, NK cell effector functions have been linked with to a number of miRNAs, including miR-155[132134], miR-150 [128,135], miR-181 [127], and miR-29 [136,137], miR-27a-5p [138], miR-30c-3p [139], miR-30e [124], miR-378 [124], miR-132 [140], miR-200a [140], miR-212 [140], miR-15b [141], miR-122 [141], and miR-362-5p [123] (Table 1). The majority of these miRNAs regulate classical effector molecules, including granzyme B and perforin, as well as the prototype NK cell cytokine IFN-γ.…”
Section: Microrna Regulation Of Nk Cell Gene Expression and Translmentioning
confidence: 99%